Формирование конечно-элементной модели металлоконструкции углеперегружателя - Гусев, Ю. Б.; Шкода, В. А.; Танченко, Андрей Юрьевич (НТУ "ХПИ", 2007)
У статті описана технологія формування параметричних скінченно-елементних моделей металоконструкції вуглеперевантажувача. Наведені приклади побудованих моделей та результати розв’язання тестових задач про власні коливання та напружено-деформований стан.

Technology of forming of parametrical finite-elements models of coal-loader hardware is described in the article. The examples of the built models and results of solution of test problems of own vibrations and stressedly-deformed state are presented.
Keywords: проектирование углеперегружателя; опытная эксплуатация; износ подтележных путей; автоматизированная генерация